INFLUENCE OF INTERESTEREFICATION REACTION IN PHYSICAL AND CHEMICAL CHARACTERISTICS OF SOYBEAN OIL AND HYDROGENATED SOYBEAN OIL BLENDS - O. F. Abdulaziz (Mesopotamia Journal of Agriculture)
This study deals with the blends of hydrogenated soybean oil to low iodine value (HS), with Soybean oil (SB), in ratio 20:80,40:60,60:40,80:20% fat to oil. Each blend was divided in to tow groups , the first one was saved under frizzing and the others was interesterified. Characterizations of these blends were done Which include Fatty Acids (FA) , FA in position sn2 and Tri Acyl Glycerol (TAG) composition, physical and chemical properties which include melting and slip melting points, penetration force, solid fat index (SFI), iodine value, refractive index, trans fatty acids (TFA) ratio and oxidative stability. Obtained results of these characterizations compared among esterified and non interesterified blends.The factor interesterefication reaction affecting on the properties of the blends were studied. The results showed that the reaction factor affected on most TAG ratios, some TAG were appeared, and others disappeared, the largest influence of reaction in the 2nd and 3ed ratio of blending , The results showed that the interesterefied fats has fatty acids' random distribution. The reaction affected on all physical and chemical characteristics, except iodine value and total FAs ratio, the results showed that there was some decrees in the means of TFA in SB with HF blends , Also showed that peroxide number with increasing time of storage for the blends before reaction is less than after reaction.